2009
DOI: 10.1254/jphs.08068fp
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Baclofen on Alterations in the Sleep Patterns Induced by Different Stressors in Rats

Abstract: Abstract. We have previously reported that sleep patterns are significantly affected by both physical and psychological stress induced by a communication box ; however, the mechanism by which stress alters sleep patterns was not established. In the present study, we investigated the role of γ-aminobutyric acid (GABA), acting through the GABA B receptor, on stress-induced changes in sleep patterns. Our results show that physical stress increased the total wakefulness time by increasing sleep latency and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Some studies reported that baclofen treatment was associated with sleep disturbance among AUD patients (44, 63). These findings are supported by preclinical evidence showing that baclofen may alter normal sleep patterns in animal models (126, 127). As AUD patients often suffer from disturbed sleep [particularly during AWS; APA (3)], it is possible that baclofen treatment may increase the risk and/or severity of sleep disorders among AUD patients.…”
Section: Baclofen (Off-label) Use For the Treatment Of Moderate To Sesupporting
confidence: 59%
“…Some studies reported that baclofen treatment was associated with sleep disturbance among AUD patients (44, 63). These findings are supported by preclinical evidence showing that baclofen may alter normal sleep patterns in animal models (126, 127). As AUD patients often suffer from disturbed sleep [particularly during AWS; APA (3)], it is possible that baclofen treatment may increase the risk and/or severity of sleep disorders among AUD patients.…”
Section: Baclofen (Off-label) Use For the Treatment Of Moderate To Sesupporting
confidence: 59%
“…Emotional experiences during the day can alter sleep quality and macrostructure in many ways [ 13 ]. For example REM sleep has been reported to be enhanced [ 14 ], shortened [ 15 ] or unchanged due to different stressors. More fragmented sleep, longer sleep latency, shorter sleep duration also frequently occurs following stressful events [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…6,7) The majorˆnding being that REM sleep was enhanced signiˆcantly by the psychological stress of communication box, and these results diŠer from other psychological stress as listed in Table 1. Therefore, these discrepancies interested us, and we therefore conducted further research to clarify the possible mechanism.…”
Section: Conclusion and Implicationmentioning
confidence: 92%
“…Sleep recording was performed after 1 h of psychological stress. 6,7) Consequently total REM sleep was signiˆcantly enhanced due to the prolonged average duration of REM sleep episodes without aŠecting the total number of REM sleep episodes. However, there was no alteration of total NREM sleep and wakefulness in rats after 1 h of psychological stress ( Table 2).…”
Section: Sleep and Psychological Stressmentioning
confidence: 99%